Comparative Analysis of Rice Farming Using Tabela and Transplantation Patterns in Harapan Village - Zulkarnain Bokingo; Meity Melani Mokoginta; Yusriyah Atikah Gobel; Dewa Oka Suparwata (STIE Amkop Makassar, 2026)
This study aims to determine the production costs and income of lowland rice farming using the Tabela planting pattern and the shifting planting pattern in Harapan Village, Wonosari District. This study involved 41 rice farmers. The research method is a survey, using a farming analysis that provides an explanation of the large production costs and income of lowland rice farming in the table planting pattern and the shifting planting pattern in Harapan Village. The results of the study show Based on the results of the analysis that has been carried out, it can be seen that the average farming costs incurred by rice farmers with a shifting planting pattern are Rp. 10,600,959 (Per Kg / Farmer / MT) and the average farming costs incurred by rice farmers with a Tabela planting pattern are Rp. 2,676,347 (Per Kg / Farmer / MT) in Harapan Village, Wonosari District, and the average income of rice farmers with a shifting planting pattern is Rp. 22,289,950 (Per Kg / Farmer / MT) and the average income of rice farmers with a Tabela planting pattern is Rp. 32,313,126 (Per Kg / Farmer / MT) in Harapan Village, Wonosari District